Hubungan antara Beban Kerja dengan Kelelahan Kerja pada Pedagang Sayur di Pasar Kota Baru Bojonegoro - Ni'matul Ulfa; Abdul Rohim Tualeka (Universitas Airlangga, 2023)
Background: The Labor Law has regulated various aspects of the protection of workers, one of which is occupational health and safety (K3). There are several factors that can trigger work accidents, one of which is fatigue and the informal sector is one of the sectors that has a high risk of experiencing work fatigue. Work fatigue can occur due to several factors, such as an unergonomic sitting work position, namely the wrong and static working position for a long time, an unequal ratio of working time and rest time, taking workload based on will not individual ability and psychological factors. High workload triggers a decrease in endurance, work efficiency and effectiveness, as well as a reduction in work capacity. Objectives: The purpose of this research is to analyze the relationship between the workload of vegetable traders at Pasar Kota Baru Bojonegoro and complaints of fatigue. Methods: An observational analytic design and used a cross sectional approach to 68 respondents. Physical workload can be assessed through pulse, mental workload is assessed through the NASA-TLX Questionnaire, and work fatigue is assessed using the SSRT Questionnaire issued by IFRC which was then analyzed using by Spearman correlation non-parametric test. Results: The majority of respondents were women (94.1%), aged in the early elderly category, namely 46 to 55 years (36.8%), had an elementary school education/MI/equivalent (42.6%), and had worked as a vegetable seller > 5 years (95.6%), has a workload (mental) in the moderate category (67.6%), has a workload (physical) in the low category (100%) and experiences work fatigue in the moderate category (63.2%). The results of the relationship test using the Spearman test showed that there was no significant relationship between (physical) workload and work fatigue with a sig. α = 0.469 and there is a relationship between workload (mental) and work fatigue for vegetable traders at Pasar Kota Baru Bojonegoro with a sig. α 0.042 and there is a weak relationship between workload (mental) and work fatigue with sig. α = 0.247. Conclusions: There is no relationship between workload (physical) and fatigue and there is a relationship between workload (mental) and work fatigue. Strong relationship is included in the weak category. Even so, these two factors must still be considered so that occupational diseases (PAK) and work-related accidents (KAK)